Five new species and a new country record in American Cerambycidae Coleoptera) - Galileo, Maria Helena M.; Santos-Silva, Antonio (Zootaxa, 2016)
Five new species are described from American fauna: Stizocera boliviensis and Sphaerion lingafelteri from Bolivia (Elaphidiini); Ectenessa wappesi from Panama (Ectenessini); Mecometopus martinsi from Peru and Ecuador (Clytini); Recchia volcanensis from Bolivia (Aerenicini). The new species are included in previous keys. Sphaerion rusticum Burmeister, 1865 is recorded from Bolivia for the first time.